An Analysis of Cookery Vocational High School Students in Studying Vocabulary through Web Blog Article - Tikiawati Tikiawati; Muchlas Suseno (Universitas Muhammadiyah Semarang, 2023)
The significance of vocabulary in reading achievement is generally acknowledged. The growth of word reading and reading comprehension abilities is influenced by vocabulary development. Several researches that study on the benefits of blogging on reading suggests that using blogs improves reading processes, creates good attitudes of reading, facilitates group discussion, and develops reading skills and critical thinking abilities. This study entitled